Ancyronyx reticulatus and A. pulcherrimus, two new riffle beetle species from Borneo, and discussion about elmid plastron structures (Coleoptera: Elmidae) - Kodada, Ján; Jäch, Manfred A.; Jr, Fedor Čiampor (Zootaxa, 2014)
Two new species of Ancyronyx Erichson, 1847 (Coleoptera: Elmidae) are described from Borneo: A. pulcherrimus (Brunei) and A. reticulatus (Sabah). Habitus views, illustrations of important characters as well as plastron structures of Ancyronyx reticulatus are presented and discussed.